Sonic Hedgehog mutations are not a common cause of congenital hypopituitarism in the absence of complex midline cerebral defects. (22nd September 2014) - Paulo, Sabrina Soares; Fernandes‐Rosa, Fábio L.; Turatti, Wendy; Coeli‐Lacchini, Fernanda Borchers; Martinelli, Carlos E.; Nakiri, Guilherme S.; Moreira, Ayrton C.; Santos, Antônio C.; de Castro, Margaret; Antonini, Sonir R.
Summary Context and Objective Sonic Hedgehog (SHH) and GLI2, an obligatory mediator of SHH signal transduction, are holoprosencephaly (HPE)‐associated genes essential in pituitary formation. GLI2 variants have been found in patients with congenital hypopituitarism without complex midline cerebral defects (MCD). However, data on the occurrence of SHH mutations in these patients are limited. We screened for SHH and GLI2 mutations or copy number variations (CNV) in patients with congenital hypopituitarism without MCD or with variable degrees of MCD. Patients and Methods Detailed data on clinical, laboratory and neuroimaging findings of 115 patients presenting with congenital hypopituitarism without MCD, septo‐optic dysplasia or HPE were analysed. The SHH and GLI2 genes were directly sequenced, and the presence of gene CNV was analysed by multiplex ligation‐dependent probe amplification (MLPA). Results Anterior pituitary deficiency was found in 74% and 53% of patients with SOD or HPE, respectively. Diabetes insipidus was common in patients with HPE (47%) but infrequent in patients with congenital hypopituitarism or SOD (7% and 8%, respectively). A single heterozygous nonsense SHH mutation (p.Tyr175Ter) was found in a patient presenting with hypopituitarism and alobar HPE. No other SHH mutations or CNV were found. Nine GLI2 variations (8 missense and 1 frameshift) including a homozygous and a compound heterozygous variation were found in patients with congenital hypopituitarism or SOD, but not in HPE patients. No GLI2 CNV were found. Conclusion SHH mutations or copy number variations are not a common cause of congenital hypopituitarism in patients without complex midline cerebral defects. GLI2 variants are found in some patients with congenital hypopituitarism without complex midline cerebral defects or septo‐optic dysplasia. However, functional analyses of these variants are needed to strengthen genotype–phenotype relationship.